Analisis Curahan Waktu Kerja Rumahtangga Petani Padi Lahan Kering di Kabupaten Sukabumi - Endang Tri Astutiningsih (Seminar Nasional Lahan Suboptimal, 2018)
Astuti et al, 2019. Time Allocation Analysis of Upland Rice Farm  Households in Sukabumi Regency. pp. 281-286.  This study aimed to analyze time allocation of household upland rice farm in Sukabumi regency. This study uses a survey method with the location of the study and the respondent farmers are chosen deliberately. The results showed that non-agricultural activities play an important role for the rural economy, especially for upland rice farm households, their roles not only in income but also in the allocation of household work. Time allocation of male labor is higher than female labor, both in agricultural and non-agricultural activities.